Transcending the National in Migration History in North America - Takai, Yukari (Labour / Le Travail, 2016)
The article reviews and comments on several books including "Beyond the Nation?: Immigrants’ Local Lives in Transnational Culture," edited by Alexander Freund, "Making the Chinese Mexican: Global Migration, Localism, and Exclusion in the U.S.-Mexico Borderlands," by Grace Peña Delgado, and"Ethnic Elites and Canadian Identity: Japanese, Ukrainians, and Scots, 1919–1971," by Aya Fujiwara.